1983
DOI: 10.1002/ctpp.19830230404
|View full text |Cite
|
Sign up to set email alerts
|

Metastable Decomposition of Ar3+ Cluster Ions Into Ar2+ and Ar+

Abstract: In this note we present the first account of a study of metastable (unimolecular decay) and collision‐induced dissociation of Ar3+ cluster ions using an experimental setup consisting of a molecular beam‐electron impact ion source and a double focussing (reversed Nier Johnson geometry) mass spectrometer. The existence of the following metastable decay processes (accessible by our sampling time window) could be demonstrated: Ar3+* → Ar2+ and Ar3+* → Ar+. The processes were studied as a function of electron impac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

1984
1984
1995
1995

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(4 citation statements)
references
References 14 publications
1
3
0
Order By: Relevance
“…The dimer fragmentation can be explained by simply counting the six available states of Ar2+,59 from which two are repulsive, leading immediately to Ar+. If we assume equal populations of the excited states, a fragmentation probability of 1:3 results, quite close to the experimental value 60. If this explanation is correct, systems with similar behaviordeep dimer ion well depths and shifted minimum distances compared with those of the neutral clusters-should show a similar fragmentation pattern.…”
supporting
confidence: 79%
“…The dimer fragmentation can be explained by simply counting the six available states of Ar2+,59 from which two are repulsive, leading immediately to Ar+. If we assume equal populations of the excited states, a fragmentation probability of 1:3 results, quite close to the experimental value 60. If this explanation is correct, systems with similar behaviordeep dimer ion well depths and shifted minimum distances compared with those of the neutral clusters-should show a similar fragmentation pattern.…”
supporting
confidence: 79%
“…Lines drawn through the experimental points have been obtained from least-squares fits, and metastable fractions obtained by extrapolating to zero pressure are statistically significant nonzero values. dissociation rates obtained for Ar" cluster ions with n-A and 7<«<10 for fragmentations in the first field-free region [reaction (3)] and successive fragmentations in the first and second field-free region, respectively [i.e., reaction (7)]. Several conclusions and points follow from these data:…”
Section: 15mentioning
confidence: 84%
“…As mentioned before, the aim of the present study is to see, from realistic calculations, how competitive the RP channels could be in speeding up (or further slowing down) the lifetimes of the metastable cluster states observed experimentally. [8][9][10][11] This effect requires the knowledge of the diatomic energy content, i.e., the various asymptotic thresholds for the rotational levels populated after breakup, and furthermore the calculation of the bound states of the triatomic complex and of its metastable states. The actual RR potential energy surface will then provide the necessary coupling.…”
Section: Results From Quantum Dynamicsmentioning
confidence: 99%
“…6 In particular, the photodissociation of argon cluster ions by electron bombardment has provided a wide variety of data 7 on the possible electronic states involved and on the relative lifetimes of the observed photofragments. Moreover, Mark and co-workers 8 have demonstrated a while ago that small argon clusters comprised of as few as three atoms can display metastable decays in time regimes extending beyond 10 /-ts after the ionization event. Since it was also found that even the dimer ion 9 could display long-time metastability, it has been suggested that centrifugal effects could be responsible for such unusually long lifetimes 10 ,1l in the trimer clusters.…”
Section: Introductionmentioning
confidence: 99%